2016
DOI: 10.1038/nn.4243
|View full text |Cite
|
Sign up to set email alerts
|

Efficient codes and balanced networks

Abstract: Recent years have seen a growing interest in inhibitory interneurons and their circuits. A striking property of cortical inhibition is how tightly it balances excitation. Inhibitory currents not only match excitatory currents on average, but track them on a millisecond time scale, whether they are caused by external stimuli or spontaneous fluctuations. We review, together with experimental evidence, recent theoretical approaches that investigate the advantages of such tight balance for coding and computation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
510
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(562 citation statements)
references
References 77 publications
29
510
0
Order By: Relevance
“…Nevertheless, a decrease in GABAergic neurotransmission has been observed in MS. 33 In fact, previous neural mass model-based studies have shown that even a small loss of interneurons, and thus a small drop in inhibitory activity, can induce a very large functional effect on hubs and the entire brain network. 34 However, given that excitatory neurons are most likely also affected by MS, it seems that a lower inhibitory activity could not be the only mechanism that underlies functional brain changes. For instance, a late and possibly ineffective attempt at beneficial functional reorganization cannot be excluded as an explanation for our results at this time.…”
Section: Structural Brain Measures White Matter (Wm) Lesions Werementioning
confidence: 99%
“…Nevertheless, a decrease in GABAergic neurotransmission has been observed in MS. 33 In fact, previous neural mass model-based studies have shown that even a small loss of interneurons, and thus a small drop in inhibitory activity, can induce a very large functional effect on hubs and the entire brain network. 34 However, given that excitatory neurons are most likely also affected by MS, it seems that a lower inhibitory activity could not be the only mechanism that underlies functional brain changes. For instance, a late and possibly ineffective attempt at beneficial functional reorganization cannot be excluded as an explanation for our results at this time.…”
Section: Structural Brain Measures White Matter (Wm) Lesions Werementioning
confidence: 99%
“…Increased conductance can reduce gain whilst making the membrane faster, extending bandwidth, and ensuring that action potentials occur more reliably. Balanced excitatory and inhibitory synaptic currents, which occur in many cortical neurons in vivo (reviewed in [48]), demonstrate the impact of synaptic conductances on energy efficiency. Computational modelling shows that single compartments receiving balanced excitatory and inhibitory synaptic currents achieve similar information rates to those receiving only excitatory inputs (or balanced excitatory and inhibitory conductances) but do so with fewer action potentials and, therefore, lower energy consumption [47].…”
Section: Synaptic Inputsmentioning
confidence: 99%
“…Graded potentials encode more information per unit time that pulsatile codes, and the conversion from graded to pulsatile produces information loss accompanied by a drop in energy efficiency [8,49,50]. Computational models show that information loss is due to increased intrinsic noise and non-linearity produced by the channels generating the action potential, as well as the duration of the action potentials themselves, which obscure the underlying graded signal [48]. Reduced efficiency is a consequence of information loss coupled with the cost of generating action potentials.…”
Section: Synaptic Inputsmentioning
confidence: 99%
“…While some of these studies have been performed using spiking networks, they still use effectively a rate-based approach in which a given input activity vector is interpreted as the firing rate of a set of input neurons (Eliasmith et al., 2012; Diehl & Cook, 2015; Guergiuev et al., 2016; Neftci et al., 2016; Mesnard, Gerstner, & Brea, 2016). While this approach is appealing because it can often be related directly to equivalent rate-based models with stationary neuronal transfer functions, it also largely ignores the idea that individual spike timing may carry additional information that could be crucial for efficient coding (Thalmeier, Uhlmann, Kappen, & Memmesheimer, 2016; Denève & Machens, 2016; Abbott, DePasquale, & Memmesheimer, 2016; Brendel, Bourdoukan, Vertechi, Machens, & Denéve, 2017) and fast computation (Thorpe, Fize, & Marlot, 1996; Gollisch & Meister, 2008). …”
Section: Introductionmentioning
confidence: 99%